Assessment of Educational Digital Game-Based Learning and Academic Performance of Grade Six Pupils (American Journal of Interdisciplinary Research and Innovation, 2024)
Digital games have surpassed the movie box office and are making their way to revolutionize the contemporary teaching methods of today’s classrooms. Educators, parents, and policymakers are debating its effect on the students, and more researchers are offshooting to prove its effectiveness and suitability for the recent digital natives. This study, therefore, found empirical evidence underpinning the efficacy of Educational Digital Game Learning on the learners’ academic performance, specifically in English concepts, using a quasi-experimental control group and descriptive design. Two classes of grade VI students were involved and labeled as the control and experimental group. During the study, the researcher used a validated test instrument. The researcher also filmed how EDGBL was conducted in the classroom and recorded interviews with experienced students. Frequency counts, percentages, weighted mean, and t-tests for independent samples were used to investigate the aims and establish the results. The findings revealed that students who underwent Educational Digital Game-Based Learning had improved their academic performance in learning English concepts. It was also found that those students who were exposed to EDGBL developed more positive habits in learning English. In contrast, those exposed to the traditional method tended to misbehave and have a monotonous learning environment. Moreover, conducting EDGBL as a method requires teachers to have practical facilitating skills to maintain solid work coordination throughout the implementation of EDGBL.